2008
DOI: 10.1002/eqe.775
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of SDOF real‐time hybrid testing systems with explicit integration algorithms and actuator delay

Abstract: SUMMARYReal-time hybrid testing is a method that combines experimental substructure(s) representing component(s) of a structure with a numerical model of the remaining part of the structure. These substructures are combined with the integration algorithm for the test and the servo-hydraulic actuator to form the real-time hybrid testing system. The inherent dynamics of the servo-hydraulic actuator used in real-time hybrid testing will give rise to a time delay, which may result in a degradation of accuracy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…Chen and Ricles [61] developed an unconditionally stable explicit integration algorithm for RTHT using a discrete transfer function approach (known as the CR method).…”
Section: Explicit Numerical Integration Techniquesmentioning
confidence: 99%
“…Chen and Ricles [61] developed an unconditionally stable explicit integration algorithm for RTHT using a discrete transfer function approach (known as the CR method).…”
Section: Explicit Numerical Integration Techniquesmentioning
confidence: 99%
“…In the real-time hybrid simulations presented herein, u d and ω where assumed equal to the expected damper deformation from the SDP and the first mode cyclic frequency of the building, respectively. Preliminary real-time hybrid simulations showed that the response results where insensitive to small variations of the selected values of u d and ω. Chen and Ricles [32] showed that it is necessary to include the damping and stiffness of the complete structure in Eq. (3) to ensure that the integration parameters result in maintaining a stable solution.…”
Section: Real-time Integration Of the Equations Of Motionmentioning
confidence: 99%
“…This time delay is usually referred to as actuator delay and will result in a desynchronization between the measured restoring forces from the experimental substructure(s) and the integration algorithm in a real-time hybrid simulation. Studies on the effect of actuator delay [31,32] show that actuator delay is equivalent to creating negative damping, which can destabilize a real-time hybrid simulation if not compensated properly.…”
Section: Actuator Delay Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…This time delay is usually referred to as actuator delay and will result in a desynchronization between the measured restoring forces from the experimental substructures and the integration algorithm in a real-time hybrid simulation. Studies on the effect of actuator delay (Wallace et al 2005, Chen andRicles 2008b) have shown that actuator delay is equivalent to creating negative damping and can destabilize a real-time hybrid simulation if not compensated properly.…”
Section: Real-time Integration Of the Equations Of Motionmentioning
confidence: 99%